Enrollment of Diverse Populations in the INGENIOUS Pharmacogenetics Clinical Trial - Shah-Williams, Ebony; Levy, Kenneth D.; Zang, Yong; Holmes, Ann M.; Stoughton, Christa; Dexter, Paul; Skaar, Todd C. (Frontiers in Genetics, 2020)
Recruitment of diverse populations and subjects living in Medically Underserved Areas and Populations (MUA/P’s) into clinical trials is a considerable challenge. Likewise, representation of African-Americans in pharmacogenetic trials is often inadequate, but critical for identifying genetic variation within and between populations. To identify enrollment patterns and variables that predict enrollment in a diverse underserved population, we analyzed data from the INGENIOUS, (Indiana GENomics Implementation and Opportunity for the UnderServed), pharmacogenomics implementation clinical trial conducted at a community hospital for underserved subjects (Safety net hospital,) and a statewide healthcare system (Academic hospital). We used a logistic regression model to identify patient variables that predicted successful enrollment after subjects were contacted and evaluated the reasons that clinical trial eligible subjects refused enrollment. In both healthcare systems, African-Americans were less likely to refuse the study than non-Hispanic Whites (Safety net, OR =0.68, p<0.002; Academic hospital, OR=0.64, p<0.001). At the Safety net hospital, other minorities were more likely to refuse the study than non-Hispanic Whites (OR=1.58, p<0.04). The odds of refusing the study once contacted increased with patient age (Safety net hospital, OR=1.02, p<0.001, Academic hospital, OR=1.02 p< 0.001). At the Academic hospital, females were less likely to refuse the study than males (OR=0.81, p=0.01) and those not living in MUA/P’s were less likely to refuse the study than those living in MUA/P’s (OR=0.81, p=0.007). The most frequent barriers to enrollment included not being interested, being too busy, transportation, and illness. A lack of trust was reported less frequently. In conclusion, African-Americans can be readily recruited to pharmacogenetic clinical trials once contact has been successfully initiated. However, health care initiatives and increased recruitment efforts of subjects living in MUA/Ps are needed. Enrollment could be further enhanced by improving research awareness and knowledge of clinical trials, reducing time needed for participation, and compensating for travel.